Implementation and Evaluation of Peer Ambassador Support to Patients Newly Diagnosed With Hematological Cancer and Their Caregivers - Kristina Holmegaard Noerskov; Iben Husted Nielsen; Emma Skov Rahbæk; Sarah Halbro; Astrid Østergaard Mortensen; Ulrik Malthe Overgaard; Karin Piil; Mary Jarden (Nursing Research and Practice)
Trial Registration: ClinicalTrials.gov identifier: NCT03493906 and NCT04039100.